NSV 05513 = 69 (Δ) UMA A LONG PERIODIC ECLIPSING VARIABLE? - Bryukhanov, I. S.; Askirko, V. M. (Одеські астрономічні публікації, 2017)
The star NSV 05513 is suggested to be an eclipsing variable with a period of 1030m - 1180m(1115m) and a range 3.m3-4.m3 V.